Criminal law - Judy Hails Kaci (Copperhouse Pub. Co., 2001)
Criminal law instructors have had a never-ending debate over what to teach first. Evolved from the old Smith's Review, Kaci's approach leads the student to an understanding of the sources of law and basic legal principles prior to delving into the complexities of American criminal law. There are ample federal and state statutes, along with pertinent briefed cases. This succinct book provides the required background and foundation to understand criminal law within the reader's scope of comprehension. The reader progresses quickly from topic to topic with the cases and statutes cementing the application and interpretation found in modern law